Prevalence of dry eye disease in visual display terminal workers: a systematic review and meta-analysis. Issue 1 (14th January 2016) - Courtin, Romain; Pereira, Bruno; Naughton, Geraldine; Chamoux, Alain; Chiambaretta, Frédéric; Lanhers, Charlotte; Dutheil, Frédéric
Abstract : Objective: To evaluate the prevalence and risk factors of dry eye disease (DED) in workers using visual display terminals (VDT). Design: Systematic review and meta-analysis. Data sources: We searched PubMed, Cochrane Library, Embase and Science Direct databases for studies reporting DED prevalence in VDT workers. Results: 16 of the 9049 identified studies were included, with a total of 11 365 VDT workers. Despite a global DED prevalence of 49.5% (95% CI 47.5 to 50.6), ranging from 9.5% to 87.5%, important heterogeneity (I 2 =98.8%, p<0.0001) was observed. Variable diagnosis criteria used within studies were: questionnaires on symptoms, tear film anomalies and corneoconjunctival epithelial damage. Some studies combined criteria to define DED. Heterogeneous prevalence was associated with stratifications on symptoms (I 2 =98.7%, p<0.0001), tears (I 2 =98.5%, p<0.0001) and epithelial damage (I 2 =96.0%, p<0.0001). Stratification of studies with two criteria adjusted the prevalence to 54.0% (95% CI 52.1 to 55.9), whereas studies using three criteria resulted in a prevalence of 11.6% (95% CI 10.5 to 12.9). According to the literature, prevalence of DED was more frequent in females than in males and increased with age. Conclusions: Owing to the disparity of the diagnosis criteria studied to define DED, the global prevalence of 49.5% lacked reliability because of the important heterogeneity. We highlight the necessity of implementing common DED diagnostic criteria to allow a more reliable estimation in order to develop the appropriate preventive occupational actions.